From Landscape to Roofscape: Pavilions for Okana - Laura Katharina Strähle; Ellen Rouwendal (Spool, 2018)
Landscape to Roofscape shows the development of a flourishing community centre, located in the centre of the small village Okana in West Kenia. The feasibility and potential of the student project triggered the design for a sustainable and innovative pavilion to grow far beyond a theoretical level. The design is based on field research on cultural patterns and local architecture, in which interviews, sketches, literature research, and the work in 1:1 scale models were used as data source. Directly after graduation, the students managed to construct the project together with local builders and an international group of volunteers in just four months. Within less than two years from initial idea to finished construction, the design fulfils its goals towards creating architecture with a strong societal impact on poorer parts of the world.